REVERSIBLE IMPOTENCE IN MIXED CONNECTIVE TISSUE DISEASE: A RARE CASE REPORT - KAKAR, ZUE; AZIZ, W; HANIF, M; FAZAL, S; KUMAR, S; REHMAN, OU (Biological and Clinical Sciences Research Journal, 2023)
Recently, phacovitrectomy, which is the combination Mixed connective tissue disease (MCTD) was first described by SHARP and COLLEGUES in 1972. The clinical and laboratorial manifestations overlap with those of SLE, Scleroderma and Polymyositis, along with presence of higher titers of antibodies against antigen, U1-RNP. We report a rare case of MCTD, who presented with all the known features along with prominent complaint of impotence. This impotence responded dramatically to the usual management of MCTD which included a combination of steroids, HCQ and Methotrexate.